MANAJEMEN KOMUNIKASI KRISIS HOAX BANK MANDIRI BANGKRUT (Studi Kasus Pada Corporate Secretary Bank Mandiri Kantor Pusat Jakarta) - Mega Fradina, (2020)
On August 13th 2019, a hoax spread on social media that could make a bad reputation, that Bank Mandiri would go bankrupt, losing Rp. 9,000,000,000,000 and will be taken over by China. This study examines the crisis communication management of Bank Mandiri's Corporate Secretary related to that hoax with Coombs's crisis management and crisis communication model which consists of pre-crisis, crisis, and pre-crisis stages. Data collection techniques by doing interviews with 3 of Bank Mandiri Corporate Secretaries and the documentations collected from screenshots of related news from the Internet. The findings obtained are at the pre-crisis stage, crisis identification is carried out, the crisis stage is clarified to overcome the hoax, and the post-crisis stage is an effort to restore the reputation by submitting Bank Mandiri conditions to stakeholders and holding One Day One News activities. . Understand the crisis, time, establish good relationships with stakeholders, teamwork, etc. are the factors that are considered the most important in crisis communication management related to the hoax.